2020
DOI: 10.18632/aging.103192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential novel differentially-expressed genes and their role in invasion and migration in renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) remains one of the most common cancer types globally, and while it has been extensively studied, the molecular basis for its pathology remains incompletely understood. Herein, we profiled three previously published datasets (GSE66272, GSE100666, and GSE105261) in a single integrated analysis aimed at identifying disease-associated patterns of gene expression that may offer mechanistic insight into the drivers of this disease. We pooled expression data from 39 normal kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…After construction of protein-protein interaction network of DEGs, we used CytoHubba to identify the hub genes with degree > 10 and further screened the hub genes to obtain candidate genes related with the prognoses of ccRCC by synthesizing the results of UALCAN, GEPIA and HPA. The results showed that TIMP1, PCK1, HMGCS2, G6PC, FBP1, ACAA1, HADH, HAO2, TGFBI, RRM2 and SUCLG1 are of prognostic signi cance in ccRCC patients, which were consistent with results of previous researches [33][34][35][36][37]. Whereafter, we veri ed the mRNA and protein expression of these genes in different ways, thus obtained three target genes, namely PCK1, HMGCS2 and RRM2.…”
Section: Rrm2 Expression Was Correlated With Immune In Ltration and Immunological Checkpoint In Ccrccsupporting
confidence: 88%
“…After construction of protein-protein interaction network of DEGs, we used CytoHubba to identify the hub genes with degree > 10 and further screened the hub genes to obtain candidate genes related with the prognoses of ccRCC by synthesizing the results of UALCAN, GEPIA and HPA. The results showed that TIMP1, PCK1, HMGCS2, G6PC, FBP1, ACAA1, HADH, HAO2, TGFBI, RRM2 and SUCLG1 are of prognostic signi cance in ccRCC patients, which were consistent with results of previous researches [33][34][35][36][37]. Whereafter, we veri ed the mRNA and protein expression of these genes in different ways, thus obtained three target genes, namely PCK1, HMGCS2 and RRM2.…”
Section: Rrm2 Expression Was Correlated With Immune In Ltration and Immunological Checkpoint In Ccrccsupporting
confidence: 88%
“…The analysis of GO processes associated with the genes whose levels of expression are not altered during tumor progression ( HIG2 , INHBB , TYROBP , STC2 , CXCR4 , NNMT , FN1 , PFKP , SLC16A3 , C1QA , and CD36 ) indicates that these genes are activated in the initial phase, and maintained at all stages of development of ccRCC metabolic and inflammatory processes and positive regulation of the multicellular organismal process. These functional features of ccRCC have been noted in previous studies ( 56 58 ); however, we identified their early onset and its preservation at all stages of tumor development, which was not previously described.…”
Section: Discussionsupporting
confidence: 51%
“…The Cancer Genome Atlas (TCGA) database ( https://tcga-data.nci.nih.gov/tcga/ ) was used to acquire publicly available messenger RNA (mRNA) profiles and corresponding clinicopathological data from 539 ccRCC tissues and 72 adjacent normal samples, Information recorded included: sex; race; laterality; tumor, node classification, and metastasis classification; tumor, node metastasis (TNM) stage; histologic grade; tumor status; relapse; and vital status. Differentially expressed genes (DEGs) were identified from TCGA database and GEO datasets ( http://www.ncbi.nlm.nih.gov/geo/ ) (including GSE15641 [ 25 ], GSE36895 [ 26 ] and GSE40435 [ 27 ], as well as GSE105261 [ 28 ]) through the “DEseq2” package and via the “Limma” package, respectively. The thresholds were |log2-fold change (FC)| >2.0 and false discovery rate (FDR) <0.01 [ 29 ].…”
Section: Methodsmentioning
confidence: 99%